Solving problems of production process. A case study in a battery making factory / Ahmad Fakhrul Amin Mohd and Janting Nyanggau - Mohd, Ahmad Fakhrul Amin; Nyanggau, Janting (1996)
This project presents analysis of problem solving of production process in a battery making factory. A case study selected was in Century Battery (M) Sdn. Bhd., in Petaling Jaya. This study concerntrated on techniques to overcome the problems of in their production process namely: Plate Shedding, Plate Cutting And Lug Cleaning, Tank Deformation and Plant Layout.